2023
DOI: 10.3390/en16041661
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Laminae for China Lacustrine Shale Oil Enrichment: A Review

Abstract: The laminar structure of shale system has an important influence on the evaluation of hydrocarbon source rock quality, reservoir quality, and engineering quality, and it is receiving increasing attention. A systematic study of the lamina structure is not only of great scientific significance but also of vital practical importance for shale oil production. In this paper, the identification and description classification of shale laminae are first reviewed. Multiple scales and types indicate that a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Thus, we suggest that an application of CO 2 adsorption should be avoided in shale oil reservoir analysis in order to reduce expenses and analysis time. In reality, it is noteworthy that laminae play a prominent role in the process of shale oil storage, migration, and production. ,,, Accordingly, it is particularly important and urgent to establish a new full-scale characterization method that can comprehensively evaluate restricted pores, free pores, and even laminar structures for shale oil reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we suggest that an application of CO 2 adsorption should be avoided in shale oil reservoir analysis in order to reduce expenses and analysis time. In reality, it is noteworthy that laminae play a prominent role in the process of shale oil storage, migration, and production. ,,, Accordingly, it is particularly important and urgent to establish a new full-scale characterization method that can comprehensively evaluate restricted pores, free pores, and even laminar structures for shale oil reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments and core and outcrop observations have indicated that the presence of horizontal fractures in the shale can cause substantial anisotropy variations with loading stresses [33][34][35]. Geological studies have also confirmed the importance of horizontal fractures for sweet spot predictions in shale reservoirs [36][37][38][39]. Accordingly, some efforts have been made to predict the VTI anisotropy of the shale based on rock physical modeling using logging data [40].…”
Section: Introductionmentioning
confidence: 99%